Plastic strain localization and fracture mechanisms of metals subjected to dynamic loading - Sokovikov, Mikhail Albertovich; Bayandin, Yuriy Vitalievich; Lyapunova, Elena Arkadievna; Plekhov, Oleg Anatolievich; Chudinov, Vasiliy Valerievich; Naimark, Oleg Borisovich (Computational Continuum Mechanics, 2013)
The mechanisms responsible for instability and localization of plastic shear during dynamic deformation of metals are investigated. The instability mechanisms are related to the collective effects in the ensemble of microshears in the regions of space localization. In-situ infrared scanning of the instability region and the analysis of the dislocation substructure confirm the suggestion about the key role of non-equilibrium transitions in the ensembles of defects for the localized plastic flow evolution. Equations that describe the relationships between the non-equilibrium transitions and the mechanisms of structural relaxation and plastic flow are used to model the plastic shear instability.